2020
DOI: 10.1186/s13019-020-01360-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of endobronchial ultrasound-guided transbronchial needle aspiration in the diagnosis and treatment of mediastinal lymph node tuberculous abscess: a case report and literature review

Abstract: Background This study aimed to report the experience of diagnosis and treatment of one rare case of mediastinal lymph node tuberculous abscess (MLNTA) using endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). Case presentation An 18-year-old female patient was hospitalized in the Affiliated Hospital of Xuzhou Medical University in November 2017, due to intermittent left chest pain. She was suspected of infecting tuberculosis (TB) and thus received anti-TB treatment. Since April 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Non-traumatic MA, which can be caused by hematogenous or lymphatic spread from distant sites of infection, or direct extension along contiguous anatomic pathways and fascial planes such as peritonsillar or retropharyngeal abscess (12), odontogenic infection, mediastinal lymph node tuberculous abscess (13) and S. aureus pneumonitis (14), is rare in children. The most common etiology identified in non-traumatic mediastinitis is S. aureus (9, 10), manifesting as disseminated staphylococcal infection (15).…”
Section: Discussionmentioning
confidence: 99%
“…Non-traumatic MA, which can be caused by hematogenous or lymphatic spread from distant sites of infection, or direct extension along contiguous anatomic pathways and fascial planes such as peritonsillar or retropharyngeal abscess (12), odontogenic infection, mediastinal lymph node tuberculous abscess (13) and S. aureus pneumonitis (14), is rare in children. The most common etiology identified in non-traumatic mediastinitis is S. aureus (9, 10), manifesting as disseminated staphylococcal infection (15).…”
Section: Discussionmentioning
confidence: 99%
“…EBUS-TBNA is a minimally invasive sampling strategy for the diagnosis of mediastinal lesions using real-time ultrasound monitoring [6,7]. Outside of its ability of tissue acquisition, recent studies have reported therapeutic application of EBUS-TBNA in mediastinal abscess, which is minimally invasive and allows for the combination of other methods to achieve better outcomes [2][3][4]8]. Casal et al [3] were the first to use EBUS-guided needle aspiration for treating infected mediastinal bronchogenic cyst.…”
Section: Discussionmentioning
confidence: 99%
“…EBUS may have a therapeutic role in the drainage of tubercular abscesses, a rare complication of colliquation of multiple lymph nodes [ 104 ].…”
Section: Causes Of Mediastinal Lymphadenopathymentioning
confidence: 99%